Monitoring the Quality of Lentik Water in Delingan Reservoir, Karanganyar, Central Java - Callista Fabiola Candraningtyas (LPPM Institut Studi Islam Sunan Doe, 2024)
Inland waters are waters that are found on the surface of the land and are generally located above sea level. Most of the water on the land comes from rainwater. Inland waters are widely used by humans to support their survival, such as for eating, drinking, cooking, bathing, and irrigation. This study aims to monitor the quality of lentic waters in the Delingan Reservoir and to know the sampling technique and analysis of physical parameters, chemistry, and biology of lentic waters. The data analysis performed was beginning with conducting research in the Delingan Reservoir, Java Province Center, then the results obtained are processed into information. The results obtained from this study are known water quality parameters and their values ​​consisting of pH, Dissolved oxygen, conductivity, salinity, TDS, turbidity, depth, and oxidation-reduction potential at four different coordinates.